Reflexive Pronoun Deixis in Harry Bradbeer’s “Enola Holmes 2 (2022)” Movie - Amanda Revia Salsabila Ahmad; Deny Kuswahono; Yulis Setyowati (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
Deixis is referring to something depending on the speaker's and addressee's current time, location, and context through an utterance. In this study, the writer focused on the analysis of the reflexive pronoun deixis. The aims of the study are to find out the reflexive pronoun deixis and the function of the reflexive pronoun deixis found in the Enola Holmes 2 movie. This research applied qualitative descriptive methods and analyzed based on the deixis types by Levinson (1983). The data used for this research was acquired by analyzing the utterances spoken by the characters in the movie. The steps to analyze the data included: (1) identifying the reflexive pronoun deixis by classifying the data into first-person reflexive pronoun, second-person reflexive pronoun, and third-person reflexive pronoun, (2) interpreting and describing the findings, and (3) drawing a conclusion of its findings. The writer found 18 data of reflexive pronoun deixis in the Enola Holmes 2 movie. References found in this research were; myself, ourselves as first-person reflexive pronoun deixis; yourself, yourselves as second-person reflexive pronoun deixis; and herself, themselves as third-person reflexive pronoun deixis. The result showed that the most dominant reflexive pronoun deixis found in this research is the second-person reflexive pronoun deixis, where the character gives advice to another character, so people who like watching films can get moral value from the conversation of the movie.